Lightweight Scheme for Secure Signaling and Data Exchanges in Intelligent Precision Agriculture - Thekaa Ali Kadhim; Zaid Ameen Abduljabbar; Hamid Ali Abed AL-Asadi; Vincent Omollo Nyangaresi; Zahraa Abdullah Ali; Iman Qays Abduljaleel (Cryptography)
Intelligent precision agriculture incorporates a number of Internet of Things (IoT) devices and drones to supervise agricultural activities and surroundings. The collected data are then forwarded to processing centers to facilitate crucial decisions. This can potentially help optimize the usage of agricultural resources and thwart disasters, enhancing productivity and profitability. To facilitate monitoring and decision, the smart devices in precision agriculture must exchange massive amounts of data across the open wireless communication channels. This inadvertently introduces a number of vulnerabilities, exposing the collected data to numerous security and privacy threats. To address these issues, massive security solutions have been introduced to secure the communication process in precision agriculture. However, most of the current security solutions either fail to offer perfect protection or are inefficient. In this paper, a scheme deploying efficient cryptographic primitives such as hashing, exclusive OR and random number generators is presented. We utilize the Burrows–Abadi–Needham (BAN) logic to demonstrate the verifiable security of the negotiated session keys. In addition, we execute an extensive semantic analysis which reveals the robustness of our scheme against a myriad of threats. Moreover, comparative performance evaluations demonstrate its computation overheads and energy consumption efficiency.